Sedação para eletroencefalografia com dexmedetomidina ou hidrato de cloral: estudo comparativo do padrão do eletroencefalograma e dos efeitos clínicos - Magda Lourenco Fernandes (2013)
Sedation for electroencephalography in subjects incapable of cooperating with the instructions is a controversial issue, since most of the sedatives, hypnotics and general anesthetics can interfere with the brain's electrical activity. Chloral hydrate (CH) is usually used for this sedation, and recently, dexmedetomidine (DEX) has been tested because preliminary data suggests that this drug does not affect the EEG. The aim of this study was to evaluate and compare the use of these two drugs for sedation during electroencephalography to test the hypothesis that both produce similar effects. Seventeen patients were evaluated during sedation with DEX or CH on separate occasions. We have compared the qualitative variables (sleep phases and baseline activity) and the quantitative variables (density, duration and amplitude of sleep spindles, spectral power and dominant frequency). Efficacy, hemodynamic and adverse effects of the drugs, duration of the procedure and time of awakening of individuals were also compared. The results demonstrated that baseline activity, density, duration and amplitude of sleep spindles did not differ between DEX and CH. Absolute power was higher in delta and theta bands and lower in alpha and mainly beta bands in exams performed with DEX. Dominant frequency in beta was similar. The total power was higher with CH. This drug also showed lower efficacy. Airway obstruction was more frequent with HC, but other adverse effects were similar. The heart frequency was lower with DEX and blood pressure did not differ. Duration of the procedure was lower with DEX but time of awakening was similar. In conclusion, the variations of the power did not change EEG baseline activity and sleep spindle characteristics, which were similar between DEX and CH. DEX has the advantage of greater efficacy and shorter duration of the procedure. Although these findings confirm that both drugs may be used for sedation during EEG, this study highlights that their behavior on the power of brain waves is not similar, leading to new investigations in order to compare the effects of these drugs on the EEG pattern.